Strengthening Maternal Education on Preventing Stunting and Gastrointestinal Disorders in Children for Sustainable Health - Maya Putri; Rizky Pratama; Dwi Arianne (Journal of Community Action, 2026)
Stunting and gastrointestinal disorders in children remain significant public health concerns, particularly in developing countries. Maternal education plays a crucial role in addressing these issues by equipping mothers with the necessary knowledge to prevent malnutrition and related diseases. This study explores the impact of maternal education programs focused on stunting prevention and gastrointestinal health for children. The intervention involved a series of workshops aimed at educating mothers about proper nutrition, hygiene practices, and recognizing early symptoms of stunting and gastrointestinal disorders. Pre- and post-intervention surveys assessed changes in knowledge, attitudes, and practices. The results showed a significant improvement in maternal knowledge regarding the importance of balanced nutrition, exclusive breastfeeding, and the prevention of infections that contribute to gastrointestinal issues. Additionally, there was a noticeable decrease in the incidence of stunting and gastrointestinal disorders in children within the target communities. This study highlights the importance of strengthening maternal education as a sustainable approach to improving child health outcomes. It emphasizes the need for ongoing education and support to ensure that preventive measures against stunting and gastrointestinal disorders are consistently practiced, ultimately contributing to long-term public health improvements.